Electro-thermo-convection in dielectric liquid subjected to partial unipolar injection between two eccentric cylinders - Elkhazen, Mohamed Issam; Hassen, Walid; Öztop, Hakan Fehmi; Kolsi, Lioua; Al-Rashed, Abdullah A. A. A.; Borjini, Mohamed Naceur; Ali, Mohamed E. (Emerald Group Publishing Ltd, 2019)
Purpose The purpose of this work is to highlight the effects of partial unipolar injection on electro-thermo-convection (ETC) in dielectric liquid contained between two eccentric cylinders. Design/methodology/approach A finite volume method was used to solve governing equations. The study is performed for different parameters, such as radius ratio (0.2 <= Gamma <= 0.6), dimensionless electric Rayleigh number (0 <= T <= 900), eccentricity (-0.4 <= e <= 0.4) and thermal Rayleigh number (10 <= Ra <= 5.105). Findings It is found that heat transfer increases with increase in dimensionless electric Rayleigh number and eccentricity ratio. Originality/value The originality of this work is to analyze the ETC in dielectric liquid subjected to partial unipolar injection between two eccentric cylinders
Keywords: Heat transfer; Eccentric cylinders; Electro-thermo-convection; Unipolar injection